Reconstruction of the Railway Station Building in Świebodzice as the Avant-Garde of the Modern Renovation. Architecture of the Building Space in the Context of the Credibility Feeling Space - Gąsowska-Kramarz, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The social being, human, is a spatial creature whose habitation space is called the residential microenvironment. An architectural object is a place in a separate space. The object-place in space is formed in a variety of ways, but so that it can only be a framework for events, without a specific definition and manner of implementation. Architecture is a form of separating space and constructing it from material and immaterial components.
Keywords: renovation; railway station; real space; simulacrum space; renowacja; dworzec kolejowy; przestrzeń realna; symulakra; Świebodzice